Pengaruh Rehabilitasi Kardiovaskular terhadap Kapasitas Fisik pada Pasien Gagal Jantung - Santoso, Richard L.; Joseph, Victor F. F.; Panda, Agnes L. (Medical Scope Journal, 2025)
Abstract: Cardiovascular rehabilitation is one of the essential management strategies recommended to enhance functional capacity of patients with heart failure. This study aimed to determine the effect of cardiovascular rehabilitation on physical capacity in heart failure patients at Prof. Dr. R. D. Kandou Hospital Manado. This was a descriptive and analytical method with a retrospective and cross-sectional design. This study involved 145 heart failure patients undergoing cardiovascular rehabilitation, of whom 48 fulfilled the inclusion criteria, while 97 were excluded. The results showed that majority of participants were male, aged 45–59 years, and had a body mass index (BMI) in the obesity I category. Most patients had hypertension, dyslipidaemia, and were prescribed ACE-I/ARB and statin therapies. Most participants' ejection fractions were classified as reduced (<40%) or mildly reduced (40–49%). Statistical analysis using the paired t-test showed significant improvements in 6-minute walk test distance, VO2 Max, and METs after cardiovascular rehabilitation (p-value <0.05 for each variable). In conclusion, cardiovascular rehabilitation significantly improved physical capacity in heart failure patients, as evidenced by increased 6-minute walk test distance, VO2 Max, and METs. These findings indicate a positive effect of cardiovascular rehabilitation on the physical capacity of heart failure patients at Prof. Dr. R. D. Kandou Hospital Manado. Keywords: cardiovascular rehabilitation; physical capacity; heart failure   Abstrak:Rehabilitasi kardiovaskular merupakan salah satu strategi penatalaksanaan penting yang direkomendasikan untuk meningkatkan kapasitas fungsional pasien gagal jantung. Penelitian ini bertujuan untuk menganalisis pengaruh rehabilitasi kardiovaskular terhadap kapasitas fisik pada pasien gagal jantung di RSUP Prof. Dr. R. D. Kandou Manado. Jenis penelitian ialah deskriptif analitik dengan desain potong lintang retrospektif. Sampel penelitian ialah 145 pasien gagal jantung yang menjalani rehabilitasi kardiovaskular; 48 pasien memenuhi kriteria inklusi dan 97 pasien dieksklusi. Hasil penelitian mendapatkan mayoritas pasien ialah laki-laki, berusia 45–59 tahun, dengan indeks massa tubuh (IMT) kategori obesitas I. Sebagian besar pasien memiliki hipertensi, dislipidemia, dan mendapatkan terapi ACE-I/ARB serta statin. Sebagian besar fraksi ejeksi pasien dikategorikan sebagai reduced ejection fraction (<40%) atau mildly reduced ejection fraction (40–49%). Analisis statistik menggunakan uji paired t-test menunjukkan peningkatan bermakna pada jarak tempuh uji jalan 6 menit, VO2 Max, dan METs setelah rehabilitasi kardiovaskular (nilai p<0,05 untuk setiap variabel). Simpulan penelitian ini ialah rehabilitasi kardiovaskular secara bermakna meningkatkan kapasitas fisik pasien gagal jantung, yang ditunjukkan oleh peningkatan jarak tempuh uji jalan 6 menit, VO2 Max, dan METs. Temuan ini mengindikasikan adanya pengaruh positif rehabilitasi kardiovaskular terhadap kapasitas fisik pasien gagal jantung di RSUP Prof. Dr. R. D. Kandou Manado. Kata kunci: rehabilitasi kardiovaskular; kapasitas fisik; gagal jantung